A new species of the leafhopper genus Satsumanus Ishihara, 1953 from India (Hempiptera: Cicadellidae: Deltocephalinae) - Sunil, Sunil; Meshram, Naresh M. (Zootaxa, 2024)
A new species of the leafhopper, Satsumanus robusta Sunil and Meshram sp. nov. of the genus Satsumanus Ishihara is described and illustrated from India.